Implementasi Literasi Budaya Kuda Kosong dalam Meningkatkan Minat Membaca pada Mahasiswa Universitas Putra Indonesia - Librilianti Kurnia Yuki (Jurnal Soshum Insentif, 2020)
Abstract. Kuda Kosong culture is related to the history of the founding of Cianjur Regency, but there are still many Cianjur people who interpret that the Kuda Kosong is associated with something mystical or magical. This is caused by the low interest of the Cianjur community to read. In addition, there is still a lack of literacy related to the history of the Kuda Kosong. This study examines the implementation of the "Kuda Kosong" cultural literacy in increasing reading interest in Putra Indonesia University students. The purpose of this study is to develop local cultural wisdom and increase reading interest in Putra Indonesia University students. This research uses a qualitative approach with descriptive research methods. Sources of data in this study consisted of students, lecturers, and education staff. Data collection techniques through interviews, observation, questionnaires, and documentation. Data were analyzed interactively consisting of data collection, data reduction, data presentation, drawing conclusions, and verification. Based on the data collected, then described and analyzed. The results showed that, 1) the implementation of the Kuda Kosong cultural literacy can motivate students to like reading activities, 2) the obstacles in the campus in increasing students' interest in reading through the implementation of the Kuda Kosong cultural literacy, namely discipline, student habituation, interests, and methods applied in reading, 3) the efforts of the campus to increase students' interest in reading through the implementation of the Kuda Kosong culture literacy is that the campus always provides information about literacy activities, introduces the importance of reading about the culture of the Kuda Kosong, and holds competitions as a forum for students to actively participate. The implementation of this research is expected to have a positive impact on fostering regional culture, especially in Cianjur Regency as a mirror of a nation. Keywords: Implementation of the "Kuda Kosong", Reading Interest. Abstrak. Budaya Kuda Kosong berhubungan dengan sejarah berdirinya Kabupaten Cianjur, akan tetapi masyarakat Cianjur selama ini masih banyak yang memaknai bahwa Kuda Kosong dihubungkan dengan sesuatu yang mistis ataupun gaib. Hal ini diakibatkan oleh masih rendahnya minat masyarakat Cianjur untuk membaca. Selain itu, masih kurangnya literasi terkait dengan sejarah Kuda Kosong. Penelitian ini mengkaji tentang implementasi literasi budaya “Kuda Kosong” dalam meningkatkan minat membaca pada mahasiswa Universitas Putra Indonesia. Tujuan penelitian ini adalah untuk mengembangkan kearifan budaya lokal dan meningkatkan minat membaca mahasiswa Universitas Putra Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian deskriptif. Sumber data dalam dalam penelitian ini terdiri dari mahasiswa, dosen, dan tenaga kependidikan. Teknik pengumpulan data melalui wawancara, observasi, angket, dan dokumentasi. Data dianalisis secara interaktif yang terdiri dari pengumpulan data, reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi. Berdasarkan data yang terkumpul, kemudian dideskripsikan dan dianalisis. Hasil penelitian menunjukan bahwa 1) implementasi literasi budaya Kuda Kosong dapat memotivasi mahasiswa untuk menyukai kegiatan membaca, 2) hambatan pihak kampus dalam meningkatkan minat membaca mahasiswa melalui implementasi literasi budaya Kuda Kosong, yaitu kedisiplinan, pembiasaan mahasiswa, minat, dan metode yang diterapkan dalam membaca, 3) upaya pihak kampus untuk meningkatkan minat membaca mahasiswa melalui implementasi literasi budaya Kuda Kosong adalah pihak kampus selalu memberikan sosialisasi mengenai kegiatan literasi, mengenalkan pentingnya membaca tentang budaya Kuda Kosong, dan mengadakan lomba-lomba sebagai wadah mahasiswa untuk berpartisipasi aktif. Dengan dilaksanakannya penelitian ini diharapkan akan membawa dampak positif bagi pembinaan kebudayaan daerah khususnya Kabupaten Cianjur sebagai cermin suatu bangsa. Kata Kunci: Implementasi Literasi Budaya “Kuda Kosong”, Minat Membaca.